Reproductive patterns of pteropodid species visiting orchards of Davao City - Malabanan, Charmaine Grace Paredes (2011)
The reproductive conditions exhibited by Pteropodid species (Ptenchirus jogori, Cynopterous brachyotis, Macroglossus minimus, ptenocherus minor, Rousettus amplexicaudatus, and haplonycteris fischeri) vising orchards of Davao City were identified and each reproductive pattern was studied. The bats wer captured wit mist nets from May 2010 to January 2011. Reproductive condition was determined by external analyses of the specimens. Female C. brachyotis suggests a polyestrous pattern; it has reproductive periods during high rainfall and high availability of durian flowers and lanzones. A polyestrous pattern is likewise exhibited by female R. amplexicaudatus, female M. minumus highly supports it of being polyestrous or being highly asynchronous. Male bats syncroniza their reproductive patterns with that of the female. The patterns of this study highly suggest their relation with climate, rainfall and flood availability in the farms.
Thesis (BS Biology) -- University of the Philippines Mindanao, 2011
Keywords: Rainfall; Reproductive patterns; Bats; Flying foxes; Old world fruit bats; Pteropodidae; Pteropodid species; Cynopterous brachyyotis; Macroglossus minimus; Ptenochirus minor; Rousettus amplexicaudatus